Reduction in C-Peptide Levels and Influence on Pharmacokinetics and Pharmacodynamics of Insulin Preparations: How to Conduct a High-Quality Euglycemic Clamp Study - Tao, Yi; Zhu, Mingxue; Pu, Junliang; Zhang, Peilin; Wan, Lei; Tang, Chengyong (Frontiers in Pharmacology, 2021)
Objective: The aim of the study was to investigate the different extent of inhibition of endogenous insulin secretion by the reduction of C-peptide levels in an euglycemic clamp study and its effects on the evaluation of pharmacokinetics, pharmacodynamics of insulin preparations, and quality of clamp study to determine the best reduction range of C-peptide levels. Methods: Healthy Chinese male volunteers were enrolled and underwent a single-dose euglycemic clamp test. Participants were subcutaneously injected with long-acting insulin glargine (0.4 IU/kg). Blood samples were collected pretest and up to 24 h post-test to assess pharmacokinetics (PK), pharmacodynamics (PD), and C-peptide levels. Results: We divided the 39 volunteers enrolled in the study into three groups according to the reduction of C-peptide levels: group A (ratio of C-peptide reduction <30%, n = 13), group B (ratio of C-peptide reduction between ≥ 30% and <50%, n = 15), and group C (ratio of C-peptide reduction ≥50%, n = 11); there were significant differences in the three groups (p= 0.000). The upper and lower limits of blood glucose oscillation in group C was statistically lower than the other groups, the range of oscillating glucose levels in group C was −17.0 ± 6.6% to −1.1 ± 6.7%. The AUC0–24 h in groups A, B, and C were 9.7 ± 2.2, 11.0 ± 2.9, and 11.9 ± 2.1 ng/ml × min, respectively, which indicated an increasing trend in the three groups (Ptrend = 0.041). For quality assessment, the average glucose (p = 0.000) and MEFTG (p = 0.001) levels in three groups were significantly different. Conclusion: The different extent of inhibition of endogenous insulin will influence the PK/PD of insulin preparations and the quality of the euglycemic clamp. Furthermore, the ratio of C-peptide reduction should be above 50% to free from the interference of endogenous insulin, and the range of blood glucose levels should be consistently maintained at −10% to 0 in the euglycemic clamp.